Sleeping beauty generated CD19 CAR T-Cell therapy for advanced B-Cell hematological malignancies - Singh, Harjeet; Srour, Samer A.; Milton, Denái R.; McCarty, Jessica; Dai, Cuiping; Gaballa, Mahmoud R.; Ammari, Mariam; Olivares, Simon; Huls, Helen; De Groot, Eleanor; Marin, David; Petropoulos, Demetrios; et al. (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T-cell therapy has emerged recently as a standard of care treatment for patients with relapsed or refractory acute lymphoblastic leukemia (ALL) and several subtypes of B-cell non-Hodgkin lymphoma (NHL). However, its use remains limited to highly specialized centers, given the complexity of its administration and its associated toxicities. We previously reported our experience in using a novel Sleeping Beauty (SB) CD19-specific CAR T-cell therapy in the peri-transplant setting, where it exhibited an excellent safety profile with encouraging survival outcomes. We have since modified the SB CD19 CAR construct to improve its efficacy and shorten its manufacturing time. We report here the phase 1 clinical trial safety results. Fourteen heavily treated patients with relapsed/refractory ALL and NHL were infused. Overall, no serious adverse events were directly attributed to the study treatment. Three patients developed grades 1-2 cytokine release syndrome and none of the study patients experienced neurotoxicity. All dose levels were well tolerated and no dose-limiting toxicities were reported. For efficacy, 3 of 8 (38%) patients with ALL achieved CR/CRi (complete remission with incomplete count recovery) and 1 (13%) patient had sustained molecular disease positivity. Of the 4 patients with DLBCL, 2 (50%) achieved CR. The SB-based CAR constructs allow manufacturing of targeted CAR T-cell therapies that are safe, cost-effective and with encouraging antitumor activity.